2022
DOI: 10.5194/acp-22-9663-2022
|View full text |Cite
|
Sign up to set email alerts
|

The ice-nucleating activity of African mineral dust in the Caribbean boundary layer

Abstract: Abstract. African mineral dust is transported many thousands of kilometres from its source regions, and, because of its ability to nucleate ice, it plays a major role in cloud glaciation around the globe. The ice-nucleating activity of desert dust is influenced by its mineralogy, which varies substantially between source regions and across particle sizes. However, in models it is often assumed that the activity (expressed as active sites per unit surface area as a function of temperature) of atmospheric minera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 106 publications
(199 reference statements)
3
18
0
Order By: Relevance
“…The singular ice-active site density approach has been used to describe both desert dust (Niemand et al, 2012;Ullrich et al, 2017;Reicher et al, 2018;Harrison et al, 2022) and the individual minerals in desert dust (Atkinson et al, 2013;Peckhaus et al, 2016;Harrison et al, 2019). Work over the last decade has demonstrated that the potassium-rich feldspars (K-feldspars) are the most active component of desert dust (Niedermeier et al, 2015;Harrison et al, 2019), a finding which contrasts with older reports where it was thought that the clay minerals dominated immersion mode freezing (Pruppacher and Klett, 2010).…”
Section: The Role Of Coarse and Super-coarse Dust Aerosols In Cloud G...mentioning
confidence: 99%
See 1 more Smart Citation
“…The singular ice-active site density approach has been used to describe both desert dust (Niemand et al, 2012;Ullrich et al, 2017;Reicher et al, 2018;Harrison et al, 2022) and the individual minerals in desert dust (Atkinson et al, 2013;Peckhaus et al, 2016;Harrison et al, 2019). Work over the last decade has demonstrated that the potassium-rich feldspars (K-feldspars) are the most active component of desert dust (Niedermeier et al, 2015;Harrison et al, 2019), a finding which contrasts with older reports where it was thought that the clay minerals dominated immersion mode freezing (Pruppacher and Klett, 2010).…”
Section: The Role Of Coarse and Super-coarse Dust Aerosols In Cloud G...mentioning
confidence: 99%
“…The concentration of dust particles that activate to ice at T, Mineral dust contains a variable quantity of K-feldspar, with desert dust particles typically containing between a few and a few tens of percent of feldspar (Atkinson et al, 2013;Perlwitz et al, 2015;Kandler et al, 2018;Harrison et al, 2022). In our calculations, we assume that the feldspar is externally mixed and that the surface area fraction is in proportion to the mass fraction of feldspar.…”
Section: The Role Of Coarse and Super-coarse Dust Aerosols In Cloud G...mentioning
confidence: 99%
“…The singular ice-active site density approach has been used to describe both desert dust (Niemand et al, 2012;Ullrich et al, 2017;Reicher et al, 2018;Harrison et al, 2022) and the individual minerals in desert dust (Atkinson et al, 2013;Peckhaus et al, 2016;Harrison et al, 2019). Work over the last decade has demonstrated that the potassiumrich feldspars (K-feldspars) are the most active component of desert dust (Niedermeier et al, 2015;Harrison et al, 2019), a finding which contrasts with older reports where it was thought that the clay minerals dominated immersion mode freezing (Pruppacher and Klett, 2010).…”
Section: The Role Of Coarse and Super-coarse Dust Aerosols In Cloud G...mentioning
confidence: 99%
“…Mineral dust contains a variable quantity of K-feldspar, with desert dust particles typically containing between a few and a few tens of percent of feldspar (Atkinson et al, 2013;Perlwitz et al, 2015;Kandler et al, 2018;Harrison et al, 2022). In our calculations, we assume that the feldspar is externally mixed and that the surface area fraction is in proportion to the mass fraction of feldspar.…”
Section: The Role Of Coarse and Super-coarse Dust Aerosols In Cloud G...mentioning
confidence: 99%
“…According to Harrison et al (2022), the ice-nucleating activity of desert dust is also influenced by its mineralogy, which varies markedly between source areas and across particle sizes. The ice-nucleating activity of African desert dust was discovered to be significantly lower than parameterisations based on soil from specific locations in the Sahara or dust sedimented from dust storms by Harrison et al (2022) from analysis of samples from the summertime marine boundary layer of Barbados taken during July and August 2017. The authors concluded that the activity of dust in Barbados' boundary layer is largely defined by the low K-feldspar content of the dust, which is around 1 %.…”
Section: Activitymentioning
confidence: 99%